Pelaksanaan Dakwah Penyuluh Agam Islam Pada Massa Pandemi Covid 19 - Wahyu Ziaulhaq (Formosa Journal of Social Sciences (FJSS), 2022)
This study describes the implementation of Islamic preaching during the Covid 19 pandemic. The purpose of this research is to educate readers that Islamic religious educators always innovate with the latest da'wah models that are adapted to the conditions of the Covid 19 pandemic. This type of research is field research. To get the desired research results, the research method that the author uses is descriptive analysis method, namely research that is directly on the object of research and then analyzed scientifically. The data collection technique that the author uses in this study is to use observation techniques, interviews. The results of the research that have been found are first, Islamic religious educators preach using media technology such as WhatsApp, Facebook, Instagram and You Tobe. Second, preaching to the yasin wiritan group by complying with the health protocols that have been set by the government, third, preaching is done in a humanist and persuasive way